Exploring the acceptability of a brief online theory-based intervention to prevent and reduce self-harm: a theoretically framed qualitative study. Issue 6 (12th November 2022) - Keyworth, Chris; Quinlivan, Leah; Leather, Jessica Z.; Armitage, Christopher J.
Abstract : Background: The volitional help sheet for self-harm equips people with the means of responding automatically to triggers for self-harm with coping strategies. Improving acceptability may be crucial to increasing effectiveness and reach. The Theoretical Framework of Acceptability (TFA) was developed to guide the assessment of intervention acceptability, but to date, no studies have applied the TFA to understand acceptability of interventions for self-harm. Aims: To apply the TFA to (a) explore people's experiences of a brief intervention to reduce repeat self-harm; and (b) understand the most prominent aspects of intervention acceptability, to make recommendations for intervention refinements and successful implementation. Method: Sixteen semi-structured interviews were conducted with people who had previously self-harmed. The TFA informed a framework analysis in which findings were mapped onto the TFA. Results: Four TFA domains were identified that were associated with acceptability of the volitional help sheet for self-harm: affective attitude, burden, intervention coherence and perceived effectiveness. People were generally positive about using the volitional help sheet (affective attitude), understood the volitional help sheet and how it worked (intervention coherence), highlighted engagement as a motivating factor in using the volitional help sheet (perceived burden) and described how the volitional help sheet could be implemented by healthcare professionals (perceived effectiveness). Conclusions: Further modifications could still be made, but it is hoped that this intervention provides a useful tool for individuals to construct their own personalised implementation intentions, and as part of longer-term support for preventing self-harm as delivered by healthcare professionals.